Immunization Campaigns and Strategies against Human Papillomavirus in Italy: The Results of a Survey to Regional and Local Health Units Representatives. (4th July 2019) - Trucchi, Cecilia; Costantino, Claudio; Restivo, Vincenzo; Bertoncello, Chiara; Fortunato, Francesca; Tafuri, Silvio; Amicizia, Daniela; Martinelli, Domenico; Paganino, Chiara; Piazza, Maria Francesca; Tassinari, Federico; Tisa, Valentino; et al.
Abstract : Objective. The study aimed to assess the impact of HPV immunization campaigns organizational aspects, the characteristics of immunization program (vaccination targets and type of offer), and communicative strategies adopted by four Italian administrative regions on vaccination coverage observed. Methods. From November 2017 to March 2018, regional and Local Health Units (LHUs) representatives were invited to complete an online survey including 54 questions evaluating vaccination invite systems, access systems to vaccination centres, reminder and recall systems, and adverse events surveillance. An overall descriptive analysis was conducted. Since observed vaccine coverage (VC) obtained in females (2002-2004 birth cohorts) was lower than objectives fixed by the Italian Ministry of Health, variables were assessed using the national VC mean obtained in the 2003 girls birth cohort as outcome. Results. Twenty-six LHUs belonging to 4 Northern and Southern Italian regions participated in the study. Organizational aspects significantly related to VC lower than the national mean were access to vaccine centres without appointment and parents' reservation as appointment planning system. Recall systems for both the first and the second dose, including the appointment in the invitation letter, the availability of regional immunization registry, and education of healthcare workers on universal HPV immunization strategies, instead, were related to higher VC. As regards preadolescent immunization strategies, both VC obtained in girls and boys were far from the Ministerial goals. Only 20% of LHUs introduced multicohort female strategies while all LHUs adopted copayment targeting both men and women. Immunizations strategies targeting subjects at risk were implemented only in half of participating LHUs. Conclusions. VC observed in participating LHUs are largely lower than the national objectives in all anti-HPV vaccine targets. Both organizational and educational strategies have to be implemented to improve the VC goals.